2020
DOI: 10.1038/s41598-020-63440-7
|View full text |Cite
|
Sign up to set email alerts
|

Rhythms of Transcription in Field-Grown Sugarcane Are Highly Organ Specific

Abstract: Circadian clocks improve plant fitness in a rhythmic environment. As each cell has its own circadian clock, we hypothesized that sets of cells with different functions would have distinct rhythmic behaviour. To test this, we investigated whether different organs in field-grown sugarcane follow the same rhythms in transcription. We assayed the transcriptomes of three organs during a day: leaf, a source organ; internodes 1 and 2, sink organs focused on cell division and elongation; and internode 5, a sink organ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 81 publications
2
9
0
Order By: Relevance
“…Tissue-specific oscillatory mechanism dominates rhythmic transcriptome in M. truncatula roots We found 30.66% oscillating transcriptomes in the shoots of M. truncatula under LL conditions, which is consistent with previous studies in A. thaliana, barley (Müller et al, 2020), sugarcane (Dantas et al, 2020), rice, and poplar (Filichkin et al, 2011). However, only 2.76% (726) oscillating transcripts were detected in the roots of M. truncatula, which is much less than the 30% oscillating leaf transcripts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Tissue-specific oscillatory mechanism dominates rhythmic transcriptome in M. truncatula roots We found 30.66% oscillating transcriptomes in the shoots of M. truncatula under LL conditions, which is consistent with previous studies in A. thaliana, barley (Müller et al, 2020), sugarcane (Dantas et al, 2020), rice, and poplar (Filichkin et al, 2011). However, only 2.76% (726) oscillating transcripts were detected in the roots of M. truncatula, which is much less than the 30% oscillating leaf transcripts.…”
Section: Discussionsupporting
confidence: 91%
“…The liver-specific oscillation could lead to larger cells and higher protein levels after feeding, promoting more effective detoxification and digestion (Sinturel et al, 2017). A previous study suggested that at least two pathways, one mediating organ specificity and the other conferring rhythmicity, could contribute to the generation of tissue-specific rhythms (Dantas et al, 2020). These two pathways are tightly coupled to modulate tissuespecific circadian rhythms, which might be necessary for the adaptation of different organs to their microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 12% of the interrogated genes presented antisense expression and in most cases, the SS/AS pairs presented co-expression [ 44 ]. The same oligo array was used to study sugarcane gene expression in several conditions [ 79 , 80 , 81 , 82 , 83 , 84 , 154 , 155 ] but the data on antisense expression was not always addressed. The antisense expression was observed in eight experimental data publications ( Table 1 ), which are briefly presented here.…”
Section: Resultsmentioning
confidence: 99%
“…In order to update the antisense expression scenario in sugarcane, we explored transcriptomic data from multiple published experiments. Eight published experiments ( Table 1 ) used the same oligo array [ 44 ] to study the gene expression of different sugarcane genotypes under greenhouse [ 44 , 79 , 80 , 81 ] or field conditions [ 33 , 82 , 83 , 84 ] and treatments such as drought and ethylene pulverization. This customized oligo array (CaneRegNet—Agilent Technologies) includes 21,901 probes in duplicate, which represent 14,522 different sugarcane-assembled sequences (SAS) from the SUCEST database (Sugarcane Expressed Sequence Tag project) [ 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…The diel regulation of the transcriptome under naturally fluctuating conditions has been investigated in crops such as rice (Oryza sativa), sugarcane (Saccharum sp. ), pineapple (Ananas comosus), and Arabidopsis species [150][151][152][153][154][155][156][157][158][159] . Investigation of 24 h changes in the transcriptome of field-grown rice found that temperature and high light intensity were major regulators of 24 h fluctuations of transcript abundance in the leaves 151 .…”
Section: Crosstalk Between Circadian and Environmental Signalling Under Natural Conditionsmentioning
confidence: 99%